Bioecology of Saline Tilapia (Oreochromis niloticus) at Different Stocking Densities in Polyculture Ponds Petta Barat, Sangihe Island Distric - Abril Siri; Sysylya Palakua; Deafranty Wengkenusa; Delfian Koneng; Yeni Indriani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Saline Tilapia (Oreochromis niloticus) cultivation in Petta Barat using extensive and monoculture cultivation techniques that low productivity and profits. To increase productivity is to cultivate in polyculture with other organisms that have high economic value, one of which is polyculture with milkfish (Chanos Chanos) using optimal stocking densities. This study aims to determine differences in stocking density on the growth of tilapia (O. niloticus) and to analyze the range of water quality values at the cultivation location. The research method Random Design Experiments with complete (RAL) used monoculture and polyculture systems. The research results obtained were different stocking densities and monoculture and polyculture cultivation systems had no significant effect on the average length, average weight, absolute length, absolute weight, and specific growth rate of saline tilapia. Meanwhile, based on water quality analysis including temperature, DO (Dissolved oxygen), TDS (Total Dissolved Solid), pH, nitrate, nitrite and ammonia are still by the standards and are still optimal for the growth of tilapia. This study concludes that at different stockings with both polyculture and monoculture systems, it does not affect the growth of tilapia so the recommendation is cultivation using a polyculture system with maximum densities.